PENYULUHAN HIPERTENSI PADA MASYARAKAT LINGKUNGAN III DAN IV KELURAHAN WINANGUN SATU KECAMATAN MALALAYANG: Hypertension Counseling In Environmental Communities III And IV Winangun Satu Village Malalayang District - Sri Seprianto Maddusa; Afnal Asrifuddin; Resika; Liliany Tatambihe; Abril Loisa Isabel Wowor; Lisnawati Valencia; Chikita Amanda Ibur Ibur; Brian Septian Palembo (Pakis Journal Institute, 2023)
Community service aims to provide knowledge and understanding to the community of Environment III and IV of Winangun Satu Village, Malalayang District regarding hypertension through hypertension counseling. Hypertension is a disease with the highest morbidity rate at the Shoulder Health Center with a total of 391 cases of Essential (Primary) Hypertension (69.4%). The lecture method is a method used in this counseling with electronic media, before the counseling is carried out the community fills out the pre-test first and the post-test after the counseling. There were 11 respondents in counseling, before counseling 3 respondents with good knowledge category became 9 respondents after counseling.